Dispersion Parameters of Thermally Deposited Thin Lithium Floride Films at Different Annealing Temperatures - Mohammed , Ghuson H. (Iraqi Journal of Science, 2023)
Thin Lithium Fluoride films have been prepared by thermal evaporation technique on glass substrate under vacuum of about 10-5mbar. The thickness of the films was 4000±50Å. The effects of annealing temperatures on the optical properties and dispersion parameters have been studies. Transmittance spectra of the films indicate that the films have high transparency. The optical absorption studies reveal that the transition is direct with band gap value varied with the annealing temperatures. Also the refractive index dispersion curves obey to the single oscillator's model. The dispersion energy and single-oscillator energy varied with the annealing temperatures